Path to Heritagization in Landscape Architecture: A Review of the Regeneration Design of Beijing Changchunyuan Park - Yufan ZHU (Fengjing Yuanlin)
ObjectiveAs a prototype of heritagization-oriented urban regeneration, the case of Changchunyuan Park epitomizes the tension between imperial garden legacy and contemporary public space demands in Beijing’s core zone. For historic cities, cultural perpetuation forms the ontological foundation of urban regeneration. It is posited that localized cultural possesses transformative potential in urban regeneration processes, particularly in regions characterized by profound historical ground. Vernacular cultural resources, though not formally recognized as institutionalized heritage, hold intrinsic developmental capacity. In this context, landscape planning and design essentially perform as heritagization mechanisms — a systematic process of transposing implicit cultural values into tangible spatial configurations. Taking the review of the regeneration design of Changchunyuan Park as a sample, this research employs a transdisciplinary approach that synthesizes historical geography, spatial semiotics and design anthropology to explore the mechanism for explicit transformation of implicit cultural value by the path to heritagization in landscape architecture. This research establishes a transferable framework for decoding cultural DNA in historic urban landscapes, while providing theoretical and practical references for stock space regeneration in areas retaining the style and features of the ancient capital.Methods/process1) Historical ground analysis: The effectiveness of historical resources is integrated hierarchically based on visible remains, measurable remains, and documentary historical grounds, anchoring the location of the Quanzhe Guild Hall in the park site and the spatial gene associated with Ji Garden, a literati garden. The historical ground characteristics of Changchunyuan Park are very evident, which situated within the Guangnei Street that archaeological evidence suggests was the location of the ancient Ji City during Zhou Dynasty (1046 – 256 BC). Xiaxie Street, the eastern boundary of the park, is a vital transport artery dating back to Jin (1115 – 1234) and Yuan (1271 – 1368) dynasties that connected Jin Zhongdu and Yuan Dadu. During Ming Dynasty (1368 – 1644), the merged upper and lower sections of this thoroughfare formed one of the oldest slanted streets in Beijing. This place is a gathering of temples and guild halls and a primary access route to Xuanwu Gate which is the southern gateway to the imperial city. As the current site of Xuannan Cultural Museum, Changchun Temple has evolved into a significant platform for promoting Xuannan culture. Undoubtedly, Changchunyuan Park adjacent to Changchun Temple is inherently bearing the same responsibility for cultural transmission. 2) Style and form selection: The traditional Beijing garden style is taken as the tone of “named composition” to regain the contemporary significance of traditional classic space. At the same time, efforts are made to focus on two types of design research that emphasize depth: One is the continuous refinement and deepening of the understanding of the essence of traditional garden culture, and the second is the potential of traditional gardens to respond to the changes in contemporary living environments. 3) Functional layout reconstruction: Through the rational deduction of site – city relationship, the park’s overall pattern of “north forest – central lake – south field” is constructed. The foundational research on historical water systems has provided strong support for the restoration of water system in the park. Despite a series of issues related to water sources, seepage prevention, and subsequent management, numerous benefits such as habitat improvement, biodiversity enhancement, and experience improvement have encouraged park design to make a groundbreaking attempt to introduce a lake of a certain scale. 4) Spatial personality shaping: The new spatial type of experimental courtyard is adapted to local conditions, and it is compatible with the attributes of urban open space and the aura of traditional classic space. The design specifically emphasizes the heterogeneity of the four directions themselves, focusing on maintaining the comprehensive openness and permeability of the four directions. 5) Design interpretation: The narrative expression of the sixteen scenes of Changchunyuan Park is explained in detail. The design scheme has significantly enhanced the park’s environmental quality, and catered to the activity needs of elderly users, children, and individuals with disabilities. Based on the cultural narrative of Ji Garden, Changchunyuan Park, a long-buried cultural heritage, has been fully reintegrated into contemporary urban life. The regeneration design plan incorporates the dimensions of ecology, people’s wellbeing, and culture.Result/conclusionThe regeneration of Changchunyuan Park is not only a spatial reconstruction, but also a “heritagization” experiment. The dual-phase construction of Changchunyuan Park serves as a critical intervention, preventing this historically significant garden from becoming another forgotten relic consigned to archival obscurity — a fate shared by numerous vanished cultural landmarks in Beijing. This research illuminates the complex dynamics of heritagization — a sociocultural process through which ordinary cultural artifacts acquire heritage status through value recognition and institutional validation. Through the review of the design process, a method paradigm of “historical ground pre-research – spatial translation of cultural symbol – dynamic precipitation of heritage value” is proposed, providing a practical sample for the stock regeneration era. The case of Changchunyuan Park demonstrates that the motivation and goal of heritagization in Landscape Architecture are not merely about designation (heritage listing), but rather about discovering, uncovering, and accumulating potential excellence. The constructed landscape becomes a palimpsest of layered meanings, facilitating emotional resonance between man and environment. Cultural heritagization should be among the missions of research and practice of landscape architecture.